Optoelectronic Devices for Vision Restoration - Wang, Victor (Curr Ophthalmol Rep, 2020)
PURPOSE OF REVIEW: The goal is providing an update to the latest research surrounding optoelectronic devices, highlighting key studies and benefits and limitations of each device. RECENT FINDINGS: The Argus II demonstrated long-term safety after five-year follow-up. Due to lack of tack fixation, subretinal implants appear to displace over time. PRIMA’s completed primate trial showed initial safety and potential for improved vision, resulting in ongoing clinical trials Bionic Vision Australia developed a new 44-electrode suprachoroidal device currently in a clinical trial. Orion (cortical stimulation) is currently undergoing a clinical trial to demonstrate safety. SUMMARY: Devices using external camera for images are unaffected by corneal or lens opacities but disconnect eye movements from image perception, while the opposite is true for implants directly detecting light. Visual acuity provided by devices is more complicated than implant electrode density and new devices aim to target this with innovative approaches.